Experiencing Breast Cancer Confronts Death but Reconciles with Life: A Qualitative Study Using Grounded Theory Methodology - Ríos-Córdoba, Diana Carolina; Figueroa-Cuesta, Juan David; Alzate-Vanegas, Sandra Isabel; Contreras-Pérez, Daniel Fernando; Yepes-Delgado, Carlos Enrique (Iatreia)
Introduction: Breast cancer is the most common oncological diagnosis in women, and experiencing it generates physical, psychological, and social demands. Objectives: To describe the meaning women construct around breast cancer and their coping strategies. Materials and Methods: A hermeneutic study with a constructivist/interpretive paradigmatic approach, based on Grounded Theory. Twenty semistructured interviews were conducted with women diagnosed with breast cancer at Hospital Pablo Tobón Uribe. The analysis utilized open and axial coding characteristic of the methodology. Results: The primary emergent meanings of breast cancer were the imminence of death and forced awareness of life's finitude. The diagnosis news generates profound uncertainty, fear of death, and the devastating effects of treatment. Some women face it alone to protect their families from suffering. Cancer highlights pre-existing life burdens: fears, situations, unresolved interpersonal relationships, or emotions difficult to manage. Cancer, as an extreme experience, improves self-relationship, enables recognition of life's essentials, and re-evaluates relationships with others. Humanized and empathetic treatment from healthcare personnel helps alleviate suffering and distress. Cancer catalyzes thoughts about the meaning of life. Conclusions: The breast cancer experience confronts death but reconciles with life, as the proximity to death triggers the necessary coping mechanisms to produce changes that allow for a more fulfilling life.